1970
DOI: 10.1139/v70-353
|View full text |Cite
|
Sign up to set email alerts
|

Gallium and indium electrode potentials in fused LiCl–KCl eutectic

Abstract: Electrode potentials of indium and gallium couples have been measured in dilute solutions of the ionic species in fused LiCI-KC1 eutectic at 450 "C.Standard molar electrode potentials of the observed couples are -1.210, -0.944, and -1.136 V against a standard molar platinum reference for the In(1)-In(O), In(II1)-In(I), and Ga(II1)-Ga(0) couples, respectively. These oxidation states and potentials are compared with previous work in this and other fused salt systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1973
1973
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
1
8
1
Order By: Relevance
“…The standard potential was calculated in the usual manner (10) and is reported with respect to the appropriate standard platinum electrode on the molar, molal, and mole fraction scales in Table I. The conventions and standard states used in this table have been described elsewhere (14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard potential was calculated in the usual manner (10) and is reported with respect to the appropriate standard platinum electrode on the molar, molal, and mole fraction scales in Table I. The conventions and standard states used in this table have been described elsewhere (14).…”
Section: Resultsmentioning
confidence: 99%
“…Mater~als.--Reagent grade lithium chloride and potassium chloride (Fisher Scientific Ltd.) were purified as previously described (10). Germanium rod (99.99%) was obtained from A.D. MacKay Inc., New York.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Electrochemistry of a gallium(III) chloride solution in high-temperature molten salts was also investigated, and the redox properties were studied. [39][40][41] Smolenskii reported briefly the electrodeposition of gallium on tungsten from 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide. 42 Electrochemistry of galium(III) chloride in air-stable ionic liquids, using in situ STM on the Au(111) electrode were carried out by Endres and co-workers, 43 and nanodeposition of gallium on Au(111) was reported by Freyland et al 44 Aiming at further studies of electrodeposition of gallium metal, we have studied buffering of the chlorogallate(III) ionic liquids.…”
Section: [Gaclmentioning
confidence: 99%
“…However, at higher In + concentrations, In + did not oxidize quantitatively. Shafir and Plambeck 64) measured electrode potentials of indium and gallium couples in dilute solutions of the ionic species in fused LiCl-KCl eutectic at 450 o C. Standard molar electrode potentials of In + /In 0 , In 3+ /In + and Ga 3+ /Ga 0 were observed. They indicated that gallium metal oxidized to Ga 3+ and oxidized Ga 3+ ion reduced to metal directly.…”
Section: Electrochemical Reactions Of Indium Metal and Indium Ions Inmentioning
confidence: 99%